2020
DOI: 10.3390/s20216108
|View full text |Cite
|
Sign up to set email alerts
|

Developing a CNT-SPE Sensing Platform Based on Green Synthesized AuNPs, Using Sargassum sp.

Abstract: Detection and quantification of diverse analytes such as molecules, cells receptor and even particles and nanoparticles, play an important role in biomedical research, particularly in electrochemical sensing platform technologies. In this study, gold nanoparticles (AuNPs) prepared by green synthesis from Sargassum sp. were characterized using ultraviolet-visible (UV-Vis) and Fourier transform-infrared (FT-IR) spectroscopies, X-ray diffraction (XRD), scanning electron microscopy (SEM), dynamic light scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…Also present at 873 cm −1 is the one-band product of C-H bending. These results suggest the involvement of phenolic compounds and polysaccharides in the synthesis of nanoparticles, as has been previously reported [30].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Also present at 873 cm −1 is the one-band product of C-H bending. These results suggest the involvement of phenolic compounds and polysaccharides in the synthesis of nanoparticles, as has been previously reported [30].…”
Section: Resultssupporting
confidence: 89%
“…Also present at 873 cm −1 is the one-band product of C-H bending. These results suggest the involvement of phenolic compounds and polysaccharides in the synthesis of nanoparticles, as has been previously reported [30]. Figure 7 shows the FTIR spectra of the ethanol-water Sargassum extract and AgNPs-S. As can be seen, both signals are similar.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Sargassum aqueous extracts for electrocatalysts and the synthesis of platinum, gold and silver nanoparticles that can be used in the construction of electrochemical glucose sensing platforms, in the catalytic activity for blue methylene degradation and as antibacterials for Staphylococcus aureus and Pseudomonas aeruginosa) [85][86][87][101][102][103] Bioremediation and purification mechanisms Effectiveness of a Sargassum-based bioremediation system for the removal of metal ions and toxic dyes in water [104] 3.2.6. Regulations and Other Strategic Lines…”
Section: Advanced Materialsmentioning
confidence: 99%
“…Some sensors have been applied to cell culture as shown in Table 1 . Moreover, a couple of studies have reported the modification of glucose sensors advanced from a commercially available screen-printed electrode (SPE) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%